Modeling Bond Yields in Finance and Macroeconomics - Diebold, Francis X; Piazzesi, Monika; Rudebusch, Glenn D (American Economic Review, 2005)
From a macroeconomic perspective, the shortterm interest rate is a policy instrument under the direct control of the central bank, which adjusts the rate to achieve its economic stabilization goals. From a finance perspective, the short rate is a fundamental building block for yields of other maturities, which are just riskadjusted averages of expected future short rates. Thus, as illustrated by much recent research, a joint macro-finance modeling strategy will provide the most comprehensive understanding of the term structure of interest rates. In this paper, we discuss some salient questions that arise in this research, and we also present a new examination of the relationship between two prominent dynamic, latent factor models in this literature: the Nelson-Siegel and affine no-arbitrage term-structure models. I. Questions about Modeling Yields 1. Why Use Factor Models for Bond Yields?—The first problem faced in term-structure modeling is how to summarize the price information at any point in time for the large number of nominal bonds that are traded. In fact, since only a small number of sources of systematic risk appear to underlie the pricing of the myriad of tradable financial assets, nearly all bond price information can be summarized with just a few constructed variables or factors. Therefore, yield-curve models almost invariably employ a structure that consists of a small set of factors and the associated factor loadings